Beach Tourism Destination Recommendation System in Padang City Using the ROC-MOORA Method - Feriantano Sundang Pranata; Yuke Permata Lisna; Retnaningtyas Susanti (Journal of Computer Science and Informatics Engineering, 2025)
Padang City's tourism sector has great potential, but there is no data-based destination recommendation system for beach tourism. This study develops a recommendation system using the Rank Order Centroid (ROC) and Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) methods. The system evaluates 10 alternative beaches based on five criteria: entrance fees, safety, operating hours, facilities, and cleanliness. Criteria weights are determined objectively using ROC, while destination rankings are calculated using MOORA. The results show that destination A4 obtained the highest score (Yi = 0.3015). This system is proven to be able to provide objective recommendations and can be implemented in the form of a web application to support the decisions of tourists and destination managers. This study contributes to the integration of the ROC-MOORA method in the tourism domain based on decision support systems.